Do incidente de desconsideração da personalidade jurídica na execução fiscal - Lui, Natália Martines (2019)
This paper addresses the challenges and incongruities brought about by the effective positivation, in the Code of Civil Procedure of 2015, by means of articles 133 a 137, the incident of disregard of legal entity, especially related to its coexistence with other autonomous branches of law, such as tax law. In this way, it presents, through legal and doctrinal analysis, the concepts and the real nature of tax law institutes, such as passive subjection, liability and redirection of tax execution, as well as the actual incident of disregard of legal entity. Afterwards, a comparison is made between the redirection of tax execution and the institute of the disregard of legal entity in order to verify the similarities and the differences between them, in terms of the legal nature. Finally, it is concluded on the possibility or otherwise of using the incident of disregard of the legal entity in the tax execution proceedings.